2017
DOI: 10.1016/j.rbre.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular injection with triamcinolone hexacetonide in patients with rheumatoid arthritis: prospective assessment of goniometry and joint inflammation parameters

Abstract: VASSw responded better at short and medium term after IAI with triamcinolone hexacetonide in our sample of RA patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 12 publications
0
12
0
3
Order By: Relevance
“…Current studies examining the effects of intra-articular steroids for patients with RA affecting the ankle have been limited. Lopes (n = 54), Cunnington (n = 25), and Furtado (n = 45) all found significant improvement in VAS score for ankle pain following IA corticosteroid injection, although length of significant pain relief varied vastly from 1 week to 12 weeks following injection [92,94,95].…”
Section: Injectionsmentioning
confidence: 98%
“…Current studies examining the effects of intra-articular steroids for patients with RA affecting the ankle have been limited. Lopes (n = 54), Cunnington (n = 25), and Furtado (n = 45) all found significant improvement in VAS score for ankle pain following IA corticosteroid injection, although length of significant pain relief varied vastly from 1 week to 12 weeks following injection [92,94,95].…”
Section: Injectionsmentioning
confidence: 98%
“…In our study, we selected joint swelling at the next visit as the outcome measure; thus, we cannot rule out the possibility that the treatment effect in injected joints was faster than that in joints receiving only systemic treatment. Previous studies have shown response to intraarticular glucocorticoids after less than 2 weeks (3,28).…”
Section: Nordberg Et Almentioning
confidence: 99%
“…Literatürde triamsinolon heksasetonidin betametazona üstün olduğunu belirten yayınlar mevcuttur (13,14). Triamsinolon heksasetonid florinize olmuş kortikosteroid türevi olup diğer steroid türevlerine göre sinoviyal sıvıda daha az çözülme özelliği ile eklem içerisinde daha uzun süre kalmaktadır ve sinovit üzerine etkisi diğer steroidlere göre daha fazladır (15). Prilokain hızlı ve kısa etkili lokal anestezik ilaçlardan olup çalışmamızda triamsinolon heksasetonid ve prilokain HCL kombine olarak kullanılmıştır.…”
Section: Gereç Ve Yöntemlerunclassified